THE INFLUENCE OF E-SERVICEQUALITY AND TRUST ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY (AN EMPIRICAL STUDY ON ONLINE SYARIAH BANKING IN INDONESIA) - Saputra, Muh Fauzan; Antonio, Ferdi (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: Regardless of the rise in the number of online banking users in Indonesia, its adoption and customers satisfaction on online banking services are still below the anticipated levels. The aim of this study is to analyze the influence of e-servicequality through its dimensions and trust on online banking toward customer satisfaction and its impact on customer loyalty. This study applied quantitative method with survey study design approach. Data are collected from Bank Syariah Indonesia (BSI) online banking customers. BSI is a result of merger between state-owned subsidiaries banks. Sample were taken purposively by online questionnaires with 1-5 Likert Scale in April 2021. The conceptual framework is tested empirically with SmartPLSâ„¢ 3.3. The result found that there are four dimensions that significantly influence customer satisfaction. Efficiency has the most significant influence on customer satisfaction. Trust has direct influence on customer satisfaction and impact toward customer loyalty. However, satisfaction demonstrated the biggest impact on customer loyalty. This study is fruitful for further academic research, as it describes the way Sharia online banking e-servicequality determinants predict customer satisfaction that is also impacting customer loyalty. The result of this study will be helpful to assist banking sector in building effective service marketing strategies.Abstrak: Terlepas dari peningkatan jumlah pengguna perbankan online, adopsi dan kepuasan pelanggan terhadap layanan perbankan online masih di bawah tingkat yang diantisipasi. Tujuan dari penelitian ini untuk meng-analisa hubungan antara dimensi kualitas layanan dan kepercayaan salam online banking terhadap kepuasan pelanggan dan dampaknya terhadap loyalitas pelanggan. Penelitian ini menggunakan kuantitatif survey. Data dikumpulkan dari nasabah BSI online banking. Bank Syariah Indonesia (BSI) merupakan hasil penggabungan dari tiga anak usaha Bank BUMN. Sampel diambil secara sengaja dengan online kuisioner dengan skala Likert 1-5 dibulan April 2021. Kerangka konseptual diuji menggunakan SmartPLSâ„¢ 3.3. Hasil dari penelitian menemukan bahwa terdapat empat dimensi yang sangat mempengaruhi kepuasan pelanggan. Efisiensi merupakan pengaruh terkuat terhadap kepuasan pelanggan. Kepercayaan memiliki pengaruh langsung kepada kepuasan pelanggan dan dampak kepada loyalitas pelanggan. Penelitian ini bermanfaat kepada penelitian akademis lebih lanjut, karena penelitian ini menjelaskan bagaimana penentu kepuasan pelanggan bank Syariah memprediksi kepuasan pelanggan dan juga mempengaruhi loyalitas pelanggan. Hasil penelitian ini akan membantu sector perbankan dalam membangun strategi marketing yang efektif.